Use of modern technology in psychiatry training in a middle‐income country. (7th December 2021) - Ouanes, Sami; Larnaout, Amine; Jouini, Lamia
Abstract: Recent advances in information technology (IT) provided us with novel teaching solutions, with the potential of a new enhanced learning experience, that is, more adapted to the needs and preferences of the younger generations of psychiatric trainees. These tools include the use of online/virtual whiteboards, live surveys/polls, live quizzes, virtual classrooms, and virtual reality. In the present paper, we describe the implementation of modern technology in psychiatric training in Tunisia, a North‐African middle‐income country. We discuss the potential benefits arising from this implementation, and we report the challenges and difficulties. Overall, the implementation of these modern technology‐based tools in psychiatric training has been successful, with a very few obstacles. It seems that the integration of these novel approaches is possible even in middle and low‐income countries without much hassle. These tools can enhance trainees' participation, motivation, and engagement, thereby potentially improving learning outcomes. Most disadvantages are related to potential technical glitches, and are likely to improve as technology progresses. Teaching is the art of tailoring the educational tools to the learning objectives and to the learners' characteristics and preferences. To achieve optimal learning outcomes, it is often needed to use a mixture of different "modern" and "less modern" techniques.